Recipe for pituitary organoids - Kano, Mayuko; Sasaki, Hiroo; Miwata, Tsutomu; Suga, Hidetaka (Frontiers in Endocrinology, 2023)
Generation of a variety of organs and tissues from human pluripotent stem cells (hPSCs) has been attempted in vitro. We here present a simple and efficient method for induction of hypothalamic and pituitary tissues from hPSCs. On provision of exogenous agents important for early hypothalamus-pituitary organogenesis, including bone morphogenetic protein 4 and activators of sonic hedgehog, in three-dimensional culture, hPSCs spontaneously form spherical organoids with two distinct tissues, hypothalamus and adenohypophysis. The pituitary tissues derived from hPSCs not only secrete adenocorticotropic hormone, but also retain both positive and negative feedback mechanisms, recapitulating mature endocrine organs in vivo. Furthermore, the results of ectopic transplantation with mouse models of hypopituitarism suggest that these hypothalamus-pituitary organoids have potential as engraftment organs. In addition to their use in transplantation for patients with hypopituitarism they will allow establishment of disease models in vitro and enable research impossible in humans. Hypothalamus-pituitary organoids promise to be a powerful tool in regenerative medicine, drug discovery, and basic research into pituitary development.